ECONOMIC JUSTIFICATION FOR TELEHEALTH TECHNOLOGY USE FOR PREVENTIVE MEDICAL EXAMINATION OF THE POPULATION IN REMOTE REGIONS - D. V. Fedyaev; V. K. Fedyaeva; V. V. Omelyanovsky (IRBIS LLC, 2015)
in this article we analysis possibility of application telemedical technologies for regular medical examination, among the adult population living far from hospitals in the Khanty-Mansi Autonomous Okrug - Yugra. The model developed medicoeconomic assumes comparison of two possible strategy of carrying out medical examination of patients with application of telemedical technologies and without it and estimates funds volume of the compulsory health insurance which came for to medical institutions. Results of research show that application of a telemedical complex allows to return costs of its acquisition due less than one and a half years to coverage increase by medical care of the handicapped and removed population of Khanty-Mansi Autonomous Okrug - Yugra.